PENERAPAN JURNALISME DAMAI DALAM PEMBERITAAN TRAGEDI KANJURUHAN DI PORTAL MEDIA ONLINE TEMPO.CO DAN SINDONEWS.COM - Faturrahman, Aditia; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine how the application of peace journalism oriented to peace, truth, society, and settlement. This study uses the theory of Robert N. framing analysis. Entman and Johan Galtung's concept of peace journalism. The research method used is, descriptive qualitative. The subject of this study online media Tempo.co and Sindonews.com, while the object of research is news about the Kanjuruhan tragedy riots in the October 2022 period. The research sample, namely the news to be analyzed, amounted to 10 news stories published in October 2022. Data collection techniques are documentation and framing analysis techniques using Robert N. Entman. The results of the study based on the results of framing Robert N. Entman, Tempo.co and Sindonews.com has applied peace journalism in its reporting. Peace orientation by exploring the formation of conflict. Orientation to truth by revealing the truth of the causes and perpetrators of conflict. Community orientation by revealing the impact of conflict on children and women, as well as giving space to peace parties. Settlement orientation by highlighting peace initiatives in the form of containing requests and demands of a number of parties. Keywords: Peace Journalism, Kanjuruhan Tragedy, Framing Analysis, Tempo.co, Sindonews.com